ANALYZING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON JOB ROLES, SKILLS REQUIREMENTS, AND EMPLOYMENT PATTERNS: A Quantitative Study of Various Industries in Phnom Penh, Cambodia - Ros, Dr. Paradise; Loeung, Dr. By (jfpublisher, 2025)
This study explores effects of artificial intelligence (AI) on Cambodia's workforce as AI becomes increasingly prevalent in work and education. Concerned about potential job displacement, the research investigates how AI is changing job roles, required skills, and employment patterns across various Cambodian industries. Using a quantitative approach, the study surveyed 435 individuals from different sectors and analyzed the data through simple and multivariate regressions. The findings indicate a strong link between AI and workforce dynamics. Specifically, task characteristics, specialized AI domain knowledge, and AI-driven information processing positively influence workforce changes. Interestingly, general AI skills and knowledge did not show a significant impact. Supplementing the quantitative data, interviews with key individuals offered insights into future of AI in employment, raising worries about job losses, data privacy issues, and unequal access. However, interviewees also acknowledged AI's potential to boost productivity and benefit both employers and employees through ethical implementation, reskilling initiatives, and collaborative approaches. The study concludes by recommending that businesses invest in strategic AI integration, specialized training, talent acquisition, and job redesign to effectively leverage the transformative power of AI.